The effects of spatial separations between water sound and traffic noise sources on soundscape assessment. (January 2020) - Hong, Joo Young; Lam, Bhan; Ong, Zhen-Ting; Ooi, Kenneth; Gan, Woon-Seng; Kang, Jian; Yeong, Samuel; Lee, Irene; Tan, Sze-Tiong
Abstract: Many studies have investigated the effects of water sound on soundscape with an assumption that target noise coincides with the masker (co-location), while no attention has been paid to spatial separations between target noise and water sound sources. This study aims to explore the effects of spatial separations between target noise and water sound on perceived loudness of target noise (PLN) and overall soundscape quality (OSQ) through laboratory experiments. Traffic noise (target) and a water sound (masker) were recorded as acoustic stimuli and a spherical panoramic video recording of a water fountain was also used as visual stimuli. The audio-visual stimuli were reproduced through a virtual reality head-mounted display and a multichannel ambisonic loudspeaker setup. The traffic noise and water sound were played simultaneously at various azimuthal separations and were combined with a panoramic recording of a water fountain as visual stimulus. Participants assessed the audio-visual stimuli in terms of PLN and OSQ. The effect of the spatial separation between the traffic noise and water sound was significant in both PLN and OSQ. Specifically, the PLN increase at 135° separation was equivalent to an estimated target noise level increment of ~1–2 dB. Similarly, the OSQ decrease at 135° and 180° separation was equivalent to an estimated target noise level increase of ~2–5 dB. Since the typical field of view of users in space is less than 135°, the results suggest that placing water features within a user's field of view could achieve better soundscape. Highlights: Spatial separation effects between water sound and traffic noise on soundscape was quantified. The spatial separation reduced effectiveness of water sound on soundscape. Perceived loudness reduction of the target noise by the water sound decreased at 135°. Soundscape quality enhancement by the water sound decreased at 135° and 180° separation.